Penerapan Media E-Book Berekstensi Epub Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa - Jannah, Ilvi Nafisatul; Hasbiyati, Haning (FKIP Universitas Islam Jember, 2020)
Based on observations of researchers on science subject teachers, it can be seen that students do not follow learning well because students are not so interested in the learning methods applied by the teacher. That the teacher had still use a method of network of the bank conventional with lectures. Therefore, the researchers tried to apply the epub-oriented e-book media to increase student motivation and learning .Thus concluded:First: The existence of the application of epub extension e-book media can increase learning motivation in students in science. The increase in learning motivation in the I & II cycle was 13% with an increase in aspects of cycle I & II, namely attention aspect 0%, 6% confidence aspect, 0% self-satisfaction aspect and 6% relevance aspect.Second: The application of epub extension e-book media can improve learning outcomes for students in science learning.